ANALISIS KINERJA SATUAN KERJA PERANGKAT KOTA (SKPK) PEMERINTAH KOTA SABANG - Irsyadi, Darwanis, Muhammad Arfan (Universitas Syiah Kuala, 2017)
Abstract: An important aspect for the purpose of regional autonomy can be achieved by improving the performance of local governments. Performance Government Agencies (SKPK) as units of local government strongly contribute to the achievement of development and improvement of services to the community. Performance is an overview of the level of achievement of the implementation of an activity, program or policy in achieving the goals, objectives, mission and vision of the organization as stated in the strategic planning of an organization. This study aims to analyze the performance of Government Agencies in the government of Sabang Municipality. This research uses descriptive analysis method. The population in this study is the whole Government Agencies in the Sabang government municipality (34 Government Agencies). In measuring scores on respondents by comparing the actual score with the ideal score to earn a percentage of the actual score. The results of this study indicate that the performance of Government Agencies in the Sabang Municipality can be expressed well, based on analysis of indicators of input, output and outcome. Keywords: performance, input, output and outcome Abstrak: Aspek penting agar tujuan otonomi daerah dapat tercapai dengan meningkatkan kinerja pemerintah daerah. Kinerja SKPK selaku unit kerja pemerintah daerah sangat berkontribusi pada pencapaian pembangunan dan peningkatan pelayanan kepada masyarakat. Kinerja adalah gambaran mengenai tingkat pencapaian pelaksanaan suatu kegiatan, program atau kebijakan dalam mewujudkan sasaran, tujuan, misi dan visi organisasi yang tertuang dalam strategic planning suatu organisasi. Penelitian ini bertujuan menganalisis kinerja SKPK di lingkungan Pemerintah Kota Sabang. Penelitian ini menggunakan metode analisis deskriptif. Populasi dalam penelitian ini adalah seluruh SKPK di lingkungan Pemerintah Kota Sabang (34 SKPK). Dalam mengukur skor atas tanggapan responden yaitu dengan membandingkan skor aktual dengan skor ideal sehingga mendapatkan persentase skor aktual. Hasil penelitian ini menunjukkan bahwa kinerja SKPK pada Pemerintah Kota Sabang dapat dinyatakan baik, berdasarkan analisis terhadap indikator input, output dan outcome.Kata kunci: kinerja, masukan, keluaran dan hasil